2009
DOI: 10.1038/ejhg.2009.29
|View full text |Cite
|
Sign up to set email alerts
|

Identification and in silico analysis of 14 novel GJB1, MPZ and PMP22 gene mutations

Abstract: Duplication within the chromosome 17p11.2 (CMT1Adup), peripheral myelin protein 22 (PMP22), myelin protein zero (MPZ) and gap junction b1-protein (GJB1) gene mutations are frequent causes of the CharcotMarie-Tooth disease (CMT). A large number of mutations in these genes are listed in databases. Sequence variants identified in patients are frequently reported as mutations without further evaluation. We analyzed 250 consecutively recruited unrelated Austrian CMT patients for CMT1Adup by microsatellite marker ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
(14 reference statements)
1
11
0
Order By: Relevance
“…We have assessed PolyPhen and SIFT [76] as alternatives to predict the effect of ferroportin mutations on protein function, because functional studies of ferroportin mutants [6,17,18,68,75] have shown conflicting results [17,18] . Our analysis shows that PolyPhen is a sensitive tool to identify disease-causing gene variants by classifying mutations identified in patients with iron overload as ‘possibly’ or ‘probably’ damaging.…”
Section: Discussionmentioning
confidence: 99%
“…We have assessed PolyPhen and SIFT [76] as alternatives to predict the effect of ferroportin mutations on protein function, because functional studies of ferroportin mutants [6,17,18,68,75] have shown conflicting results [17,18] . Our analysis shows that PolyPhen is a sensitive tool to identify disease-causing gene variants by classifying mutations identified in patients with iron overload as ‘possibly’ or ‘probably’ damaging.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this mutation reported as p.Asp195Tyr corresponds to the same position as in our patients (p.Asp234Tyr) after adapting the position after the MPZ reference sequence NM_000530. In addition, a familial case with the same mutation was recently reported,9 where disease onset in the index patient was found at 43 years of age with mild symptoms and a CMT1 phenotype. These findings indicate that this mutation can account for variable disease pathology phenotypes, including CMT1 or a mild CMT2, as indicated in our patients, as well as a variation in age at onset.…”
Section: Discussionmentioning
confidence: 83%
“…Functionally the most interesting mutant studied here is D224Y, which now has been described in at least 3 studies (Fabrizi et al 2006; Miltenberger-Miltenyi et al 2009; Schneider-Gold et al 2010). It is a gain-of-function mutant, inducing ordered lipid bilayer stacks in vitro , which are more tightly packed than those formed by wt-P0ct or the other variants.…”
Section: Discussionmentioning
confidence: 91%
“…Six known missense mutations are located within P0ct, of which four cause dominant demyelinating CMT type 1B (CMT1B). These include T216ER (Su et al 1993), D224Y (also referred to as D195Y and D234Y) (Fabrizi et al 2006; Miltenberger-Miltenyi et al 2009; Schneider-Gold et al 2010), R227S (Shy et al 2004), and the deletion of Lys236 (K236del) (Street et al 2002). In addition, K236E has been linked to dominant axonal CMT type 2I (CMT2I) (Choi et al 2004), and A221T, which was discovered as a co-mutation together with the deletion of Val42 in the Ig-like domain, was identified in a patient with DSS (Planté-Bordeneuve et al 2001).…”
Section: Introductionmentioning
confidence: 99%